Accumulation of plant antenna complexes is regulated by post-transcriptional mechanisms in tobacco. - Flachmann, R (1995)
Transgenic tobacco plants expressing antisense RNA directed against the multigene family of the light-harvesting complex of photosystem II (LHCII) were raised and analyzed biochemically and physiologically. A partial 5' terminal sequence with 509 nucleotides complementary to cab (chlorophyll a/b binding protein) genes reduced the amount of transcript to almost undectectable levels. We demonstrated for endogenous genes that a 5' terminal sequence with only 52 to 105 nucleotides complementary to the transit sequence of cab can be equally efficient in gene repression. Chlorophyll content and chlorophyll a-to-chlorophyll b ratios of thylakoid membranes isolated from transgenic plants were unchanged in comparison with the wild type. Photosynthetic oxygen evolution and in vivo-measured chlorophyll fluorescence of the transformants showed that LHCII accumulates to normal levels. The reduced level of cab mRNA did not correlate with the amount of LHCII in thylakoids. This indicates that transcriptional regulation is not the rate-limiting step in the biogenesis of the LHCII apoprotein. The antenna size of photosystem II is therefore modulated by yet undiscovered posttranscriptional mechanisms.